Preparation of European Public Health Professionals in the Twenty-first Century - Bjegovic-Mikanovic, Vesna; Otok, Robert (Frontiers in Public Health, 2017)
The public health profession in Europe has a leadership role for ensuring European’s health in the twenty-first century and therefore must assume responsibility for advancing education for research and practice. Three fundamental questions are explored: (1) What are the main public health problems facing public health professionals; (2) What are their existing competencies after training; and (3) What competencies do European employers expect? The European Schools of Public Health assessed their best success to be in the field of health promotion, followed by disease prevention including identification of priority health problems, and elimination of health hazards in the community. Conversely, they see the least success in dealing with preparedness and planning for public health emergencies. From an employer’s perspective, significant gaps between current and desired levels of performance at the job exist for all Essential Public Health Operations of World Health Organization. Based on prior research and recent European surveys of Schools and Departments of Public Health, the following recommendations are made, which emphasize the leadership role of the European public health community: (1) the preparation of public health professionals requires an interface between public health functions, competencies, and performance; (2) competence-based education is important and allows debates on the scope of the required education; (3) governments have to realize that the present lack of infrastructure and capacity is detrimental to the people’s health; (4) as public health challenges are increasingly global, educational institutions have to look beyond the national boundaries and participate in European and global networks for education, research, and practice.